2014
DOI: 10.1186/1471-2458-14-395
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of diarrhoeal disease in under-five children among health extension model and non-model families in Sheko district rural community, Southwest Ethiopia: comparative cross-sectional study

Abstract: BackgroundWorldwide diarrheal disease is the second leading cause of death in under-five year’s children. In Ethiopia diarrhoea kills half million under-five children every year second to pneumonia. Poor sanitation, unsafe water supply and inadequate personal hygiene are responsible for 90% of diarrhoea occurrence; these can be easily improved by health promotion and education. The Ethiopian government introduced a new initiative health extension programme in 2002/03 as a means of providing a comprehensive, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
149
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(202 citation statements)
references
References 11 publications
45
149
7
1
Order By: Relevance
“…Children whose mothers/caretakers had never attended school were 3.7 times and attended primary were 2.9 times more likely to have diarrheal diseases compared to those who attended tertiary level of education. This finding is similar with other studies [6,[18][19][20][21][22]. This was also supported by RDHS in 2014-2015 where it was revealed that the prevalence of diarrhea is higher among children whose mothers have no education (14 percent) or a primary education (12 percent) than among those whose mothers have a secondary education or higher (9 percent).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Children whose mothers/caretakers had never attended school were 3.7 times and attended primary were 2.9 times more likely to have diarrheal diseases compared to those who attended tertiary level of education. This finding is similar with other studies [6,[18][19][20][21][22]. This was also supported by RDHS in 2014-2015 where it was revealed that the prevalence of diarrhea is higher among children whose mothers have no education (14 percent) or a primary education (12 percent) than among those whose mothers have a secondary education or higher (9 percent).…”
Section: Discussionsupporting
confidence: 91%
“…In Ethiopia the prevalence of diarrheal disease among under-five children in a 2-week period was reported 31.0% in Arba Minch District [6], 26.1% in Hadaleala District [7], 24.9% in northwest Ethiopia [8], 22.5% in the eastern part of Ethiopia [9], 19.6% in a rural area of southern Ethiopia [10] and 18.0% in Mecha District [11]. There are different factors associated with occurrence of diarrhea among children less than five years and these differ from place to place.…”
Section: Introductionmentioning
confidence: 99%
“…A significant association was found between incidence of enteric pathogen and frequency of hand washing with soap by mother. Similar results were given by Gebru et al [28], in the comparative cross-sectional study at southwest Ethiopia, where a remarkable difference of childhood Diarrhoea were observed among children whose mothers not practiced hand washing at critical time with soap were more likely to develop Diarrhoea when compared to children whose mothers were practiced hand washing at critical time with soap. Similarly in a study by Karambu et al [23], care taker not washing hands after changing napkin can expose the child to Diarrhoea illness more than one and half times as compared to those washing hands after changing the napkins.…”
Section: Discussionsupporting
confidence: 88%
“…Unless the pool is cleaned and maintained and its water adequately treated, contamination may lead to a number of disease outbreaks such as gastroenteritis, conjunctivitis, keratitis, trachoma, otitis, cholera, dysentery, eczema, skin rashes, typhoid, dysentery, giardiasis, cryptosporidiosis, helminthiasis, cholera, hepatitis, rotavirus infection, salmonellosis, and central nervous systems associated diseases [3,[13][14][15][16][17][18][19][20][21][22][23]. The aetiologic agents of some of these diseases have been isolated from natural and domestic water sources in Uganda and are associated with devastating illnesses [9,10,24,25].…”
Section: Introductionmentioning
confidence: 99%